Plant–microbe interactions as drivers of ecosystem functions relevant for the biodegradation of organic contaminants - Fester, Thomas; Giebler, Julia; Wick, Lukas Y; Schlosser, Dietmar; Kästner, Matthias (Current opinion in biotechnology, 2014)
•Biotransformation is an ecosystem property.•Microbes are the main drivers in biotransformation.•Dispersal of chemicals and bacteria drives degradation effectiveness.•Ecosystem stability is increased by plant–microbe interactions. The plant organism and associated microbial communities can be seen as a sunlight driven hotspot for the turnover of organic chemicals. In such environments the fate of a chemical will not only depend on its intrinsic structural stability toward (bio-)chemical reactions and its bioavailability but also on the functional effectiveness and stability of natural microbial communities as main drivers of natural attenuation of chemicals. Recent research demonstrates that interactions between plants and microorganisms are crucial for the biotransformation of organic chemicals, for various processes affecting the bioavailability of such compounds, and for the stability of the affected ecosystem. Practical bioremediation approaches, therefore, should encompass integrated measures targeting functional vegetation as well as functional microbial communities. Good examples for a successful practical approach are constructed wetlands, where an artificial, simplified ecosystem is used for the detoxification of organic contaminants. While such systems have considerable practical success, they are often treated as a black box and a sound mechanistic understanding of functional resilience and of the ‘reactive power’ of such plant–microbe ecosystems is poor. This situation has to change, if progress in the application of bioremediation is to be made.